A place like home - Pilcher, Rosamunde (St. Martin's Press, 2021)
A collection of Rosamunde Pilcher's most enduring short stories, never before published in book form. The collection contains fifteen stories, which range from The Holiday, in which a wife surprises her husband of twenty-five years with a holiday full of Mediterranean sunshine, red rocks and blue seas in an effort to rekindle the romance they had before children; The Eye of Love which takes the reader to a village by the sea where old flames meet again; and A Place Like Home, where a lonely young woman goes to recuperate in a Scottish countryside after a brief illness.